L’Agence d’Antonin Raymond à Tokyo dans l’Entre-deux-guerres : enjeux, acteurs, processus - Yola Gloaguen (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In Japan, the architect is a relatively recent figure on the chessboard of construction trades. As for the profession itself, the architectural office was imported during the great transfer of knowledge and technology operated by the government during the Meiji era (1868-1912). However, importing foreign models into a local context requires many adaptations. These adaptations primarily depend on the different actors working within the office, and on their capacity to adapt, learn and collaborate with inhouse and external partners. To illustrate this issue, this article deals with the office of Czech-born American architect Antonin Raymond, during his first stay in Japan (1920-1938). During these first eighteen years, Raymond put together a team and a developed a work method that allowed him to become one of the true pioneers of modern architecture in Japan. Based on testimonies from a number of his former collaborators and the analysis of architectural drawings, this article focuses on two topics: Raymond’s key partners and their role in the development of a modern and contextual architectural practice, and some of the conception tools used for the design of private villas.